Secularização e exceção no horizonte da genealogia teológica da governamentalidade de Giorgio Agamben - Diógenes, Francisco Bruno Pereira (2019)
The two initial elements that title this work, "secularization" and "exception", indicate a possible interpretation of the so-called theological genealogy of the economy and the government of the italian philosopher Giorgio Agamben; more dense and, perhaps, central perspective of his philosophical project titled Homo sacer, whose publication began in 1995 and ended in 2015. Already appreciated as a key concept of the contemporary era, secularization is understood by Agamben as a theological signature. The author emphasizes the "strategic function" that this concept has assumed in modern culture, in so far as have always been marked by disagreements and struggles by its conceptual domain. About the category of exception from the work of the philosopher, it can be understood as a notion that expresses a fundamental structure to be recognized in various contexts, as for example the sphere of human language and the logic of sovereignty. This last is, precisely, the focus of greatest interest in this research, since it is especially the sovereign exception that allows a more fruitful understanding of the work of the author having as key to reading the preceding category, that of secularization. With the encounter of both terms, it follows a horizon of research opened by Italian philosopher, when he draws attention to the need to be aware of the theological roots of political philosophy, that is, precisely, the scope of your theological genealogy. This means that it is necessary to learn to recognize the processes of secularization by which the various forms of thought and intervention on reality passed along the history, in the contexts of philosophy, culture, government mentality and political praxis. This research, however, has focused on the fundamentals and correspondence between the two concepts, without the intention to deeply develop all aspects achieved by this genealogy of Agamben. These are the fundamental traits of bibliographical research whose results are presented in the following text.